2022
DOI: 10.3389/fcell.2022.827079
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Map of Peristaltic Waves in the Chicken Embryonic Gut Reveals Importance of Enteric Nervous System and Inter-Region Cross Talks Along the Gut Axis

Abstract: Gut peristaltic movements recognized as the wave-like propagation of a local contraction are crucial for effective transportation and digestion/absorption of ingested materials. Although the physiology of gut peristalsis has been well studied in adults, it remains largely unexplored how the cellular functions underlying these coordinated tissue movements are established along the rostral-caudal gut axis during development. The chicken embryonic gut serves as an excellent experimental model for elucidating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 25 publications
(44 reference statements)
6
19
0
Order By: Relevance
“…At E12 ( cpm), nucleation sites concentrated along distinct positions along the length of the gut ( Figures 1C,D ). The spatiotemporal maps and the spontaneous emergence of OPWs strongly resemble the results of Shikaya et al (2022) The positions of the OPWs slowly drifted with time and could even disappear ( Figure 1C ). A similar continuous drift occurring both before and after the administration of tetrodotoxin was reported in Figure 5B by Shikaya et al (2022) —because the drift is continuous I do not think it is induced by tetrodotoxin but rather reflects the natural time evolution of a purely myogenic system.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…At E12 ( cpm), nucleation sites concentrated along distinct positions along the length of the gut ( Figures 1C,D ). The spatiotemporal maps and the spontaneous emergence of OPWs strongly resemble the results of Shikaya et al (2022) The positions of the OPWs slowly drifted with time and could even disappear ( Figure 1C ). A similar continuous drift occurring both before and after the administration of tetrodotoxin was reported in Figure 5B by Shikaya et al (2022) —because the drift is continuous I do not think it is induced by tetrodotoxin but rather reflects the natural time evolution of a purely myogenic system.…”
supporting
confidence: 66%
“…In their recent article, Shikaya et al (2022) reported on the existence of preferential sites of nucleation of contractile waves along the chicken embryonic day 12 midgut, termed sites of “origin of peristaltic waves” (OPW). Histological analysis by the authors did not reveal any peculiarities of these sites compared to other locations along the gut.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The chicken embryonic gut, which is highly gene-manipulable in/ex vivo , has recently emerged as a powerful model for elucidating the endogenous potential and regulation of peristalsis-related cells including ICCs, because peristalsis occurs even though no ingested material is present in the moving gut (Chevalier et al, 2017). In addition, the distribution map of peristaltic movements along the entire gut axis is available (Shikaya et al, 2022). Previous studies using in situ hybridization with c-Kit showed that the composition of ICCs in the chicken gut largely parallel that in mammals (Chevalier et al, 2020; Lecoin et al, 1996; Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%